Biochemical characterization with kinetic studies of melanogenic enzyme tyrosinase from white button mushroom, Agaricus bisporus (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
In Agaricus bisporus, color is a key determinant for marketability and consumer acceptability. However, postharvest browning has become a major concern, affecting the overall economics of the mushroom industry. In button mushrooms, the tyrosinase enzyme (E.C.1.14.18.1) is responsible for the browning reactions by catalyzing the conversion of monophenols and diphenols into quinones which polymerize to form melanin. Thus, the present study focused on the purification and characterization of tyrosinase from A. bisporus. This enzyme was purified with a final yield of 19.71% and 32.05 purification fold. The study of enzymatic activity over a temperature (5-45°C) and pH range (3-10) showed that the optimum temperature was 35°C with pH 7. The kinetic studies revealed that Km values were different for catechol (0.71 mM) and L-dopa (0.87 mM), which indicated a higher affinity of the enzyme for catechol. Inhibition studies showed that cinnamic acid is a non-competitive inhibitor while salicylic acid is a competitive inhibitor of tyrosinase. The molecular weight of the enzyme was found to be 43 kDa and different amide regions were reflected by the FTIR spectra of the enzyme. This study may provide valuable insights into the structure, biochemical properties, and inhibition of tyrosinase enzyme for controlling mushroom browning.